If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 = 7x + -6 Reorder the terms: 29 = -6 + 7x Solving 29 = -6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 29 + -7x = -6 + 7x + -7x Combine like terms: 7x + -7x = 0 29 + -7x = -6 + 0 29 + -7x = -6 Add '-29' to each side of the equation. 29 + -29 + -7x = -6 + -29 Combine like terms: 29 + -29 = 0 0 + -7x = -6 + -29 -7x = -6 + -29 Combine like terms: -6 + -29 = -35 -7x = -35 Divide each side by '-7'. x = 5 Simplifying x = 5
| 7=m | | y/5=-2/10 | | (4b-5c)+(5a+2b)= | | w/22+22=44 | | -3(5n-5)=-5n-15 | | x^4+x^3-23x^2+3x+90=0 | | A=7B+5C | | -2=r-(5) | | z/2=z+1/3 | | -3-5/-4+(2-1) | | 4x=238 | | 72+5=9z+3 | | (6x^2+5x+7)-(2x^2-11x+12)= | | 15p/2+p=17 | | -2y=-x+2 | | 6000(1+0.07)9= | | y=1/3x+2/5 | | 8=x-(1) | | 1/5(x+3)^2-5=0 | | -3/20x=6 | | x+4y=-5 | | -4x-4=5-(7x-6) | | 5y^2-y-1=0 | | x+(x-17.8)=196.8 | | 4x/9-5=x | | 5x+5-2x=3+4 | | x-(-4x)=x+9 | | 4x^2-32x+64=3x^2-12x-36 | | 5(6x-2)+3(8-3x)-5(4x+4)=-3 | | 7-4y=3 | | -5n-6(n-5)=85 | | p=21+sw |